Kepemimpinan Kepala Madrasah dalam Mengoptimalisasi Penggunaan Media dan Pengaruhnya terhadap Motivasi Belajar Siswa MA As’adiyah No. 1 Atapange Wajo Sulawesi Selatan - Ahmad Muktamar B; Ariswanto Ariswanto; Nurnaningsih A (Departement of Mathematics Education, 2021)
Leadership plays an important role in influencing, encouraging, inviting, guiding, moving, directing people or groups to voluntarily do something towards achieving a certain goal that has been set. Likewise, the principal as a leader in the education unit plays a role in optimizing the leadership functions in schools. This study examines the role of school/madrasah principals in optimizing the use of instructional media, as well as the relationship between media use and student learning motivation. This research determines the object of research at Madrasah Aliyah As'adiyah Number 1 Atapage Wajo, South Sulawesi. To examine these problems, this research uses descriptive qualitative research methods. The data collection procedure was carried out through library research, in the form of citing books related to research, either through direct or indirect quotations. In addition, field research was carried out, by collecting data in the form of observations, interviews, documentation and questionnaires. Qualitative data were analyzed by deductive, inductive and comparative methods while quantitative data were analyzed using statistical analysis methods. The results showed that the madrasa head played a very important role in efforts to optimize the use of learning media, and the use of learning media showed a positive effect on student learning motivation, shown among other things that students were more serious about learning, concentrated, and learning was more interesting and real.